PENDANAAN KAMPANYE : ANTARA DEMOKRASI DAN KRIMINALISASI - Mery Christian Putri (Universitas Janabadra, 2017)
Election is a democratic institution that is meant to fill public positions both legislative and executive, central or regional, in a philosophical perspective improve political contract with the people. Elections are meant to establish the rule of good governance, the legislation relating to the election, Act No 8 of 2011 and Act Number 15 of 2011 meant that the election could escort the achievement of the election results, namely the realization of good and clean governance. In connection with the stretcher, the regulations on electoral funding both from APBN / APBD should be regulated carefully so as to encourage the establishment of a clean election system. Commission Regulation no. 17 in 2013 were essentially directed to realizing these goals. One of them set about their special account campaign funds are accounts that hold funds and separated from the campaign finance and personal financial account or candidates for DPR, DPD, DPRD. In the perspective of state finances, the Law No. 17 In 2013, Law NO. 1 of 2004 and Law No. 15 of 2004 has been set up on matters related to state finances. It facilitates the tracking of election funding allocation from the state budget. On the other side of the law governing the TIPIKOR can be used as a repressive instrument when proven occurrence Corruption-related crimes or money laundering. There needs to be a mechanism for integrating the paradigm of democratic elections as well as the State's financial regulatory system, including the supervision of campaign funds technocratic paradigm. This phenomenon could be the one thing that is the paradox between democracy and technocracy, but on the other hand could promote the establishment of a substantive democracy since the election that reflects the synchronization between the democratic process embodiment of good and clean governance. Be a challenge to create a democracy that requires deliberation and discretion amid efforts to use campaign funds by technocratic perspective. This paper intends to discuss efforts to promote democracy with reference to the principles of good governance. Keywords :fund, campaign, general election, democracy, political corruption